Application of the Bayesian Belief Network methodology in Tunisia for analyzing institutional performance and rangeland governance and providing empirically-based feedback on the draft pastoral code - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The method has been tested and validated using case studies in three governorates in Southern Tunisia (Medenine, Tataouine and Kebili). It has been further used to provide empirically-based feedback on the draft pastoral code for Tunisia.